Equitable faculty hiring: development and implementation of teaching faculty hiring rubrics - Arevalo, Erik; Sato, Brian K.; Lo, Stanley M.; Wilton, Mike (Frontiers in Education, 2025)
Despite the increasing diversity of undergraduate students in the United States, university faculty demographics, particularly in science, technology, engineering, and mathematics (STEM) fields, remain largely homogeneous, which is problematic for fostering an inclusive academic environment. We examined the hiring process for tenure-track teaching-focused faculty (TFF) positions, specifically within the University of California system, to develop and implement inclusive hiring practices that may promote greater faculty diversity. Through a series of faculty learning communities (FLCs), we developed and implemented inclusive hiring rubrics designed to better evaluate teaching excellence and ensure the recruitment of diverse faculty members. Our findings highlight the critical need for faculty diversity, particularly TFF who instruct in gateway introductory STEM courses, to enhance student outcomes by fostering more inclusive teaching practices and reducing racial disparities in academic achievement. We recommend that institutions adopt inclusive hiring practices, including the use of tailored hiring rubrics, to create a more equitable and supportive learning environment for all students.